Environmental Changes of the Temirnik River in Rostov-on-Don: Perubahan Lingkungan Sungai Temirnik di Rostov-on-Don - Murooj Abbas Buhlool AL-Ghizzi; Zahraa Zahraw Al-Janabi (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: The increasing anthropogenic impact on river ecosystems has raised concerns about water quality and its effects on surrounding communities. Specific Background: This study focuses on the Temirnik River, located in the northern part of the city, particularly assessing pollution levels in the beaches of